Anna, Banana, and the friendship split - Rissi, Anica Mrose (Rissi, Anica Mrose. Anna, Banana, 2015)
Anna and Sadie have always been best friends so when Sadie suddenly starts being mean, Anna is very sad and seeks support from her dog Banana and classmate Isabel, as well as advice from her brother Chuck and her parents.